Electrical Control of Electromagnetically Induced Transparency by Terahertz Metamaterial Funneling. Issue 2 (3rd December 2018) - Jung, Hyunseung; Jo, Hyunwoo; Lee, Wonwoo; Kim, Beom; Choi, Hyunyong; Kang, Moon Sung; Lee, Hojin
Abstract: Electromagnetically induced transparency (EIT) analogs using metamaterials have diverse applications, including nonlinear optics, telecommunications, and biochemical sensors. These EIT analogs can be actively controlled by embedding semiconducting materials into metamaterial structures, but most active EIT metamaterials require complex optical setups and complicated fabrication processes. Graphene‐based EIT metamaterials are some of the most promising active EIT systems because of their simple controllability by electrical bias, but related researches have so far been limited to theoretical or numerical studies. Here, experimentally verified graphene EIT metamaterials are provided by controlling the terahertz funneling of the unique metaatom structures. The proposed active EIT metamaterials are fabricated on flexible and ultrathin polyimide films to acquire the lowest substrate insertion losses and achieve a 1 ps group delay change at the transmission peak of the EIT analog. Moreover, because the proposed metamaterials exhibit resonance properties that vary depending on the polarization direction, the phase delay can be controlled up to 80° from the proposed metamaterials by rotating the incident polarization to the orthogonal direction. Overall, by controlling the group and phase delay of incident waves in a single metamaterial device simultaneously, a multifunctional active tuning system can be realized in the terahertz range. Abstract : Both group delay and phase control of terahertz waves are realized in a single device by controlling graphene‐based anisotropic metamaterials. For specific polarization, an electromagnetically induced transparency analog can be controlled by manipulating the terahertz funneling in active metamaterials, whereas the phase property can be changed by controlling the interconnection between metaatoms for orthogonal polarization.